TREATMENT OF RADIOTHERAPHY MONOISOCENTRIC TECHNIQUE IN CASES OF NASHOPHARANGEAL CANCER AT UNIT RADIOTHERAPHY INSTALLATION RADIOLOGY RSUP DR. SARDJITO YOGYAKARTA - Hafsi Afrizun Khatamsi; Rini Indrati; Emi Murniati (Jurnal Imejing Diagnostik (JImeD), 2018)
Background: Monoisocentric technique is a recomended technique for examination of nasopharangeal cancer radiotheraphy, but most hospital has not applied this technique, while in Dr. Sardjito Yogyakarta Hospita use this technique has not been done consistently because technique monoisocentric need high-precision tool and techniques monoisocentric of nasopharangeal cancer and why monoisocentric technique used in nasopharangeal cancer in Unit Radiotheraphy Instalation Dr. Sardjito Yogyakarta Hospital.Methods: This type of research is qualitative with case study approach. the data was collected in November-December 2017 at radiotherapy Installation of Dr. Sardjito Yogyakarta Hospital by observation methodology, interview with Radiation Oncologist Specialist, Medical Physiciast and Radiographer. the data obtained from the study were analyzed by an interactive model, creating the interview transcripts subsequently reduced and processed within the type of open coding, given within the type of quotations then are often drawn conclusions.Result: Base of the results of reserch in Unit Radiotheraphy Instalation Dr. Sardjito Yogyakarta Hospital, includes patient examination and staging, CT Simulator, TPS planning, geometry verification and radiotheraphy radiation process. Monoisocentric techniquebare used because  irradiation time getting faster, minimize the accurrence of hot spots and cold spot, dose distribution homogeneousConclusion: Administration of mono-centric technique of Nasopharyngeal cancer in Dr. Sardjito Yogyakarta, conducted in several stages: staging, CT simulator, TPS planning (field calculation, isocenter location, beam direction and dosage per fraction), geometry verification (comparing DRR and actual irradiation and values should not be 0.2 mm) and continued with radiotherapy radiation in LINAC treatment room. The aim of using monoisocentric technique in case of nasopharyngeal carcinoma at Radiotherapy Unit of Radiology Installation of Sardjito Yogyakarta was obtained by shorter real time irradiation time, the happening of hot spot and cold spot in the field of radiation between local field of nasopharynx and locoregional become smaller, homogeneous dose distribution.